Environmental DNA (eDNA) metabarcoding reveals strong discrimination among diverse marine habitats connected by water movement. (27th February 2019) - Jeunen, Gert‐Jan; Knapp, Michael; Spencer, Hamish G.; Lamare, Miles D.; Taylor, Helen R.; Stat, Michael; Bunce, Michael; Gemmell, Neil J.
Abstract: While in recent years environmental DNA (eDNA) metabarcoding surveys have shown great promise as an alternative monitoring method, the integration into existing marine monitoring programs may be confounded by the dispersal of the eDNA signal. Currents and tidal influences could transport eDNA over great distances, inducing false‐positive species detection, leading to inaccurate biodiversity assessments and, ultimately, mismanagement of marine environments. In this study, we determined the ability of eDNA metabarcoding surveys to distinguish localized signals obtained from four marine habitats within a small spatial scale (<5 km) subject to significant tidal and along‐shore water flow. Our eDNA metabarcoding survey detected 86 genera, within 77 families and across 11 phyla using three established metabarcoding assays targeting fish (16S rRNA gene), crustacean (16S rRNA gene) and eukaryotic (cytochrome oxidase subunit 1) diversity. Ordination and cluster analyses for both taxonomic and OTU data sets show distinct eDNA signals between the sampled habitats, suggesting dispersal of eDNA among habitats was limited. Individual taxa with strong habitat preferences displayed localized eDNA signals in accordance with their respective habitat, whereas taxa known to be less habitat‐specific generated more ubiquitous signals. Our data add to evidence that eDNA metabarcoding surveys in marine environments detect a broad range of taxa that are spatially discrete. Our work also highlights that refinement of assay choice is essential to realize the full potential of eDNA metabarcoding surveys in marine biodiversity monitoring programs.